PLANT PIGMENTS IN SOME MEDICAL PLANTS OF FAMILY LAMIACEAE (BOSNIA AND HERZEGOVINA, W. BALKANS) - Redzic, S.; Sejdic, N.; Palic, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plant pigments (chlorophyll and carotenoides) are very important group of primary metabolites. Besides their role in process of photosynthesis and plant protection from extensive radiation, they have huge appliance in pharmaceutical industry, cosmetology and dietetic. Plant pigments are also given significant role in anti-oxidant activity [1, 2]. Goal of these researches is qualitative – quantitative analysis of main and side pigments in selected medical species of wild flora in BiH, including endemic species. Plant material is gathered during different seasons. It has been transported fresh to laboratories where qualitative (paper and thin layer chromatography) and quantitative (specterphotometric) analysis was taking place. Results of researches showed significant presence of chlorophyll a, chlorophyll b and carotenoides. Ratio between chlorophyll a and chlorophyll b is rarely 3:1, as stated in classical literature but rather close to 3:2 and more, which makes these species even more medical and gives them higher potential anti-oxidant capacity [3]. References: 1. Redzic, S., Hodzic, N., Tuka, M. (2005) Bosn J Basic Med Sci. 5(2): 53-8. 2. Redzic, S., Tuka, M., Pajević, A..(2006) Bosn J Basic Med Sci. 6(2): 25-31. 3. Davies, K. ed. (2004) Plant pigments and their manipulation. Annual Plant Reviews, 14, 368p., Blackwell Publishing, Oxford.